2006
DOI: 10.1523/jneurosci.4615-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of NMDA and AMPA Glutamate Receptors on Functional Magnetic Resonance Imaging Signals and Evoked Neuronal Activity during Forepaw Stimulation of the Rat

Abstract: Most of the currently used methods for functional brain imaging do not visualize neuronal activity directly but rather rely on the elicited 1-(4-aminophenyl)-3-methylcarbamyl-4-methyl7,8-methylenedioxy-3,4-dihydro-5H-2,3benzodiazepine] significantly decreased both the hemodynamic response (BOLD, Ϫ49 Ϯ 13 and Ϫ65 Ϯ 15%; PWI, Ϫ22 Ϯ 48 and Ϫ68 Ϯ 4% for 5 and 7 mg/kg, i.v., respectively; CBV, Ϫ80 Ϯ 7% for 7 mg/kg; n ϭ 4) and the SEPs (up to Ϫ60%). These data indicate that the interaction of glutamate with its post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 70 publications
10
54
1
Order By: Relevance
“…These results indicate that in the barrel cortex NMDA receptordependent mechanisms can control the local blood flow via release of cyclooxygenase-2 generated metabolites. Similar effects of NMDA receptor inhibition on local hemodynamic parameters were also observed in the somatosensory cortex during electrical stimulation of forepaw stimulation (Gsell et al, 2006) or the ramus infraorbitalis of the trigeminal nerve (Norup Nielsen and Lauritzen, 2001) and, as shown in the current fMRI study, in the entorhinal cortex during electrical perforant pathway stimulation. Consequently, NMDA receptor-dependent mechanisms may be more important for the generation of a BOLD response in cortical areas, or, more likely, the direct perforant pathway stimulation is efficient enough to trigger hemodynamic responses via additional mechanisms.…”
Section: N-methyl-d-aspartate Receptor Inhibition Modifies the Blood supporting
confidence: 84%
See 2 more Smart Citations
“…These results indicate that in the barrel cortex NMDA receptordependent mechanisms can control the local blood flow via release of cyclooxygenase-2 generated metabolites. Similar effects of NMDA receptor inhibition on local hemodynamic parameters were also observed in the somatosensory cortex during electrical stimulation of forepaw stimulation (Gsell et al, 2006) or the ramus infraorbitalis of the trigeminal nerve (Norup Nielsen and Lauritzen, 2001) and, as shown in the current fMRI study, in the entorhinal cortex during electrical perforant pathway stimulation. Consequently, NMDA receptor-dependent mechanisms may be more important for the generation of a BOLD response in cortical areas, or, more likely, the direct perforant pathway stimulation is efficient enough to trigger hemodynamic responses via additional mechanisms.…”
Section: N-methyl-d-aspartate Receptor Inhibition Modifies the Blood supporting
confidence: 84%
“…One reason could be that the applied concentration of MK801 (i.e., 0.5 mg/kg body weight ) was not sufficient enough to inhibit NMDA-dependent processes, at least during the beginning until distribution processes are completed. In the previous paper by Gsell et al (2006), an effect of MK801 on generated BOLD responses was observed with a delay of 8 to 12 minutes, indicating that in our approach an effect of MK801 should also occur during the second block after application. During the third stimulation block, we observed a significant change of the population spike augmentation and development of the population spike latency, indicating that at this time the applied concentration of MK801 was efficient enough to modify the neuronal activities (Figures 3 and 4).…”
Section: N-methyl-d-aspartate Receptor Inhibition Modifies the Blood mentioning
confidence: 45%
See 1 more Smart Citation
“…Various anaesthetics have been tested in rats and mice for compatibility with functional activation using haemodynamic fMRI (18)(19)(20)(21)(22).…”
Section: Choice Of Anaesthesia and Effect On Brain Activationmentioning
confidence: 99%
“…In a recent extensive investigation, two ionotropic glutamate receptor antagonists working on either the N-methyl-D-aspartate (NMDA) subtype (NMDA-R) or the alpha-amino-3-hydroxy-5-methyl-4 isoxazole propionic acid (AMPA) subtype (AMPA-R) were applied during somatosensory forepaw stimulation in the rat, while electrical brain activity was recorded with somatosensory evoked potentials (SEPs) and haemodynamic response by BOLD-sensitive and CBF-sensitive fMRI (20). On the basis of their complex study design, these authors were able to analyze the differential effects of these two ionotropic glutamate receptor types on neuronal activity and haemodynamic response: the NMDA-R antagonist MK-801 only slightly diminished the SEPs but markedly reduced the haemodynamic response, indicating that NMDA-R-mediated neuronal excitation is closely connected to the haemodynamic response [e.g.…”
Section: Physiological and Molecular Basis Of Brain Activity Measuredmentioning
confidence: 99%